Current research and developments in welding of 18% nickel maraging steel. (June 2023) - Jose, Bibin; Manoharan, Manikandan; Natarajan, Arivazhagan; Muktinutalapati, Nageswara Rao; Madhusudhan Reddy, G.; Meshram, Suresh D.
Maraging steels are low-carbon, high nickel-containing precipitation-hardened steels with an excellent combination of strength and toughness. Their outstanding performance gained the increasing attention of scientists, industrialists, and end-users over the past six decades. The present global rapid growth in the consumption of maraging steel, particularly in aerospace, defense and other engineering applications, involves the fabrication of high-performance welded joints. Maraging steels offer relatively high flexibility from the welding point of view. Gas tungsten arc welding is the most preferred welding process for maraging steels. As the need for increased productivity is growing worldwide in many fields, such as aerospace, mechanical engineering, etc., where thick sections are used, issues like heat input, inter-pass temperature, cooling rate, and the selection of weld consumables become important for achieving defect-free joints. Many advanced techniques like plasma, laser, and hybrid welding processes are being developed to fulfil the requirements for joining higher thickness products without distortion. The major problem associated with welding maraging steel is the formation of reverted austenite in the fusion zone and the heat-affected zone. This problem can be mitigated by choosing optimized filler wires and the proper selection of post-weld heat treatment for the weldments. This paper extensively reviews the influence of welding processes and conditions on the microstructure and mechanical properties of maraging steels with due emphasis to structure–property relationships.